A influência da integração multissensorial na construção do espaço semântico no sistema Kansei de engenharia: um estudo de Design Ergonômico com barbeadores descartáveis - Razza, Bruno Montanari [UNESP] (2014)
In recent decades, the market of consumer products has changed from the production-oriented point of view to a more market-focused, i.e. to consumers. Today, consumers turn their attention not only to the fators logical and rational products, but increasingly symbolic and emotional factors have gained an important role in the buying decision. Some methods have already been used to design emotional significance in the products, but they still rely on the experience of the designer to understand the consumers' desires and needs and then convert them into products. In the 1970s, Nagamachi created and ergonomic method called Kansei Engineering System [KES] which establishes a relation between expectations, desires, emotions of users and product attributes. However, only recently that more advanced statistical methods have enabled this tool to be used in the development of products that meet the emotional, aesthetic and symbolic needs of the users. Recent research into user experience point to the importance of simulating more receptive senses for a better interaction since it can make it more intense, assist memorization and increase emotional bonds with the product in use. This phenomenon receives te name of multisensory integration. However, most research with SKE use only one sensory channel [vison] and it is unclear how multisensory integration in the user experience of a product can affect the reationship between user's perception and the characteristics of the product. The goal of this their is to apply the SKE to assess user's perception of disposable razors in order to identify how the expansion of sensory channels can affect the user's perception about these products. The study involved the participation of 321 users of disaposable razors and 40 products found in domestic and international market. The study involved the evalution of subjective perception using the Semantic Differential and perceived usability in three levels of...